Electronic Guide-book on the Funds of Philological Archive - Boļšakova, Nataļja (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2015)
The work is dedicated to the scientific and practical task of the creating an electronic guide to the funds of the Pskov dialect and folklore-ethnographic archive, which is stored in the scientific and educational laboratory of the Pskov State University. The relevance of the topic is due to the extension of the implementation of digital technologies in the work of archives in order to organize, secure storage of the unique information and to facilitate access to the materials for the users. The specificity of the work is that at the core of the guidebook is a specially designed electronic database, which includes the information on a number of basic information fields, due to the requirements for the registration of the field data. A special place is given to the informative part of the archival units such as expeditionary notebooks and audio recordings. As a result, the user can make a request for any of its parameters: the year of the survey, settlements, informants, collectors and by the genre-thematic approach as the most important for the researcher. The experimental model of the developed guide has been tested on the basis of the archival data from the southern historical and cultural area of the Pskov region, bordering with Belarus.